Gebiet Leningrad. Bevölkerungsdichte. ([Berlin] : Gen.-St. d. H. Abt. f. Kr. Kart. u. Verm.-W. (IV. Mil-Geo), 1941., 1941)
1:1000000.
Keywords: 1940-luku; kartat; väestö; asukastiheys; Leningrad; Leningradin alue